EXPERIMENTAL MODEL OF FORMING OF PROFESSIONAL SELF OF FUTURE PHYSICAL EDUCATION TEACHERS - Teslenkov, Alexander Yu. (Educological discourse, 2016)
Тhe article is devoted to the essence of the experimental model of professional self-organization of future teachers of physical education. which formed the basis of a formative experiment on the preparation of students for these activities. The author defines the pedagogical conditions, components, criteria and stages of formation of professional self-organization of future teachers of physical education, namely: adaptive-orientation, information processing, productively creative. The basis of the construction of the experimental model is based on a synergistic approach that allows to consider the student as an open self-organizing system that strives for self-development.